Tadib and Islamization of Knowledge: Epistemological Dialectics of Al-Faruqi and Al-Attas - Nofrizal Nofrizal; Yufrizal Yufrizal; Syahruddin Syahruddin; Riki Saputra; Sukmareni Sukmareni (International Journal of Multidisciplinary Research of Higher Education, 2026)
This article investigates the epistemological dialectics between Ismail Raji Al-Faruqi and Syed Muhammad Naquib Al-Attas, focusing on the concepts of Islamization of knowledge and ta’dib in twenty-first-century Islamic education. The study is motivated by enduring challenges such as the dichotomy of knowledge, secularization, curriculum fragmentation, digital disruption, and the crisis of adab in contemporary Islamic institutions. Using a Systematic Literature Review with thematic-comparative synthesis, it analyzes academic publications from 2020 to 2026 on Islamization of knowledge, ta’dib, adab, Islamic worldview, knowledge integration, curriculum reform, and decolonization of knowledge. The findings reveal that Al-Faruqi’s contributions emphasize Islamization of knowledge, tawhid integration, disciplinary reconstruction, curriculum development, and institutional reform. In contrast, Al-Attas is more closely associated with ta’dib, adab, the Islamic worldview, hierarchy of knowledge, and the formation of the civilized human being. Both thinkers critique secularized knowledge and the dichotomy between religious and modern sciences, yet their epistemological strategies diverge: Al-Faruqi advances an operational and institutional project, while Al-Attas provides a metaphysical and conceptual foundation. The study concludes that a critical synthesis is possible only if their fundamental differences are preserved, offering significant implications for curriculum reform, knowledge integration, and the renewal of Islamic educational philosophy in the digital era.